Development of an interactive multimedia-based training program for offensive and defensive tactics in the soccer extracurricular activity - Muhammad Aji Akbar; Afri Tantri; Samsuddin Siregar; Amir Supriadi; Jaffry Zakaria (Physical Education Departement of University PGRI Jombang, 2026)
This study aimed to develop an interactive multimedia-based training program for attacking and defensive techniques in high school soccer extracurricular activities. The study employed a Research and Development (R&D) approach based on the Borg and Gall model. Participants were students involved in soccer extracurricular activities at SMAN 1 Perbaungan and SMAN 1 Pantai Cermin. The development process included information gathering, planning, product development, field testing, revision, and implementation. Data were collected through expert validation sheets, practicality questionnaires, observations, and documentation. Product validity was evaluated by four expert validators consisting of an instrument expert, a material expert, a media expert, and a language expert. Product practicality was assessed by four soccer coaches. Data were analyzed descriptively using percentage-based criteria.The results showed that the developed multimedia program achieved a highly valid category with an average validity score of 88.73% and a highly practical category with an average practicality score of 92.85%. The product includes tactical materials, instructional videos, strategy animations, formation diagrams, and interactive learning features. Therefore, the developed multimedia program is suitable as a supporting training resource for high school soccer extracurricular activities